Growth and quality of family accommodation in the function of tourist development of Slavonski Brod - Lončarić, Biljana (Oeconomica Jadertina, 2022)
The city of Slavonski Brod has been intensively developing as a tourist destination. Although the main motives for the arrival of tourists are business and family gatherings and other types of social events, and "food and accommodation" in cases of guests in transit, tourist traffic shows a tendency to grow which implicitly leads to an increase in accommodation. From the data of the eVisitor system, it is evident that more progressive growth is recorded in non-hotel compared to hotels and similar accommodation establishments. This is primarily due to the fact that, in the circumstances of the coronavirus pandemic and the conditions in which the hospitality sector operates under the epidemiological measures, family accommodation owners continue to operate relatively well (in the period from January to December 2020 family accommodation recorded a decrease of 31,71% compared to the same period in 2019, which is even 14,27% less than the average decline at the level of all city accommodation establishments). The research goals of this paper were to determine the attitude of local population regarding apartmentization and to find out if the owners of private rooms/apartments intend to provide accommodation services in future, and/or expand/modernize existing accommodation units. In the research we applied a questionnaire among local citizens and in-depth interviews with several owners of family accommodation as methods. The hypothesis we tried to prove was that both the growth and the quality of family accommodation in a destination is in the function of its tourist development. The research results should motivate the local population that has excess living space to provide accommodation services as additional activity and assist local government units in adopting measures to encourage private entrepreneurship in tourism.